Analysis and Implementation of the Effectiveness of Independent Curriculum at the Kupompong Child Growth and Development Clinic Inclusive Education Institution in Surabaya - Bestari, Dinda; Mulyanti, Dety (Journal of Education Method and Learning Strategy, 2024)
The study aims to evaluate the effectiveness of the Independent Inclusion Curriculum in enhancing learning outcomes for students with learning difficulties, such as slow learners, and those with emotional, behavioral, and intellectual barriers, as well as ADHD. It also examines differences in curriculum implementation across various educational institutions, including therapy centers for children with special needs. This qualitative phenomenological study involved observations, interviews, and documentation at the Kupompong Surabaya Child Growth and Development Clinic. Researchers collected data from seven participants, including five psychologists and two class facilitators, who supported children aged 16-18 using the inclusive Independent Curriculum. Utilizing Nvivo software for data analysis facilitated efficient management and interpretation of qualitative data. The study found that the Independent Curriculum significantly enhanced engagement and learning outcomes for students with various disabilities. Key improvements included better social skills, increased participation in classroom activities, and higher academic achievement. The curriculum's flexible and individualized approach, incorporating adaptive teaching methods and therapeutic interventions, effectively addressed each student's unique needs. The Independent Curriculum's inclusive design successfully supports students with diverse learning difficulties by providing personalized learning plans and employing adaptive teaching methods. This research aligns with the global trend in inclusive education by promoting tolerance, respect for diversity, and integration of students with special needs into mainstream education settings. This approach benefits students with disabilities and enriches the learning experience for all students by fostering a more diverse and inclusive environment.